The importance of healthcare professionals' love and lack of love in substance abuse treatment - Shaw Waage, Magdalena; Thorkildsen, Kari Marie (Nordisk Tidsskrift for Helseforskning, 2022)
Summary Love is the most fundamental to human existence, and it is essential for health care to be perceived as caring. Substance use disorders are complex, and often characterized by self-criticism, shame and guilt. The purpose of this study was to gain a deeper understanding of patients in their addiction treatment experiences of how healthcare personnel's love and their lack of love can be expressed. Qualitative interviews were conducted with four patients who were admitted for treatment at two institutions that offer interdisciplinary specialised addiction treatment. Data were analysed using Lindseth and Nordberg's phenomenological hermeneutic method. The results showed that love is expressed as care, in that one experiences being understood, that one is met with authenticity and equality, and that one gets the help one needs. When these phenomena were absent in the relationship with the healthcare personnel, the participants felt that their dignity was violated and that it could be difficult to complete the treatment.
Keywords: love; substance use disorder; care; understanding; authenticity; equality